Undiagnosed and ‘overdiagnosed’ COPD using postbronchodilator spirometry in primary healthcare settings: a systematic review and meta-analysis - E Haydn Walters; Michael J Abramson; Shyamali C Dharmage; Kerry Hancock; Jennifer Perret; Sui Wah Sean Yip; Nur Sabrina Idrose; Nilakshi Waidyatillake (BMJ Open Respiratory Research, 2023)
Background Despite chronic obstructive pulmonary disease (COPD) being a major global cause of mortality and hospitalisation, it is often undiagnosed or inaccurately diagnosed in clinical settings.Objective To systematically synthesise all peer-reviewed papers from primary healthcare settings that have reported data on: (1) undiagnosed COPD, that is, patients with respiratory symptoms and postbronchodilator airflow obstruction consistent with COPD, without a formal clinician’s diagnosis of COPD either documented in health records or reported by patients and (2) ‘overdiagnosed COPD’, that is, clinician’s diagnosis without postbronchodilator airflow obstruction.Methods Studies investigating these diagnostic metrics in patients from primary healthcare clinics (according to predefined inclusion/exclusion criteria) were sourced from Medline and Embase and assessed for bias (Johanna Briggs Institute tools for prevalence studies and case series). Meta-analyses of studies of adequate sample size used random effect modelling stratified by risk factor categories.Results Of 26 eligible articles, 21 cross-sectional studies investigated 3959 cases of spirometry-defined COPD (with or without symptoms), and 5 peer-reviewed COPD case series investigated 7381 patients. The prevalence of spirometry-confirmed COPD without a diagnosis documented in their health records was 14%–26% in studies of symptomatic smokers (N=3). 1 in 4 patients taking inhaled therapies (25% (95% CI 22% to 28%), N=2) and 1 in 6 smokers irrespective of symptoms (16% (95% CI 14% to 18%), N=6) fulfilled diagnostic spirometry criteria but did not report receiving a COPD-related diagnosis. In an adequately powered series of COPD cases documented in primary healthcare records (N=4), only between 50% and 75% of subjects had any airflow obstruction on postbronchodilator spirometry performed by study researchers, therefore, COPD was clinically ‘overdiagnosed’ in 25%–50% of subjects.Discussion Although data were heterogeneous and of modest quality, undiagnosed COPD was common in primary healthcare, especially for symptomatic smokers and patients treated with inhaled therapies. In contrast, frequent COPD ‘overdiagnosis’ may represent treatment of asthma/reversible component or another medical diagnosis.PROSPERO registration number CRD42022295832.